Non-growing/growing season non-uniform-warming increases precipitation use efficiency but reduces its temporal stability in an alpine meadow - Han, Fusong; Yu, Chengqun; Fu, Gang (Frontiers in Plant Science, 2023)
There are still uncertainties on the impacts of season-non-uniform-warming on plant precipitation use effi-ciency (PUE) and its temporal stability (PUEstability) in alpine areas. Here, we examined the changes of PUE and PUEstability under two scenes of non-growing/growing season non-uniform-warming (i.e., GLNG: grow-ing-season-warming lower than non-growing-season-warming; GHNG: growing-season-warming higher than non-growing-season-warming) based on a five-year non-uniform-warming of non-growing/growing season experiment. The GLNG treatment increased PUE by 38.70% and reduced PUEstability by 50.47%, but the GHNG treatment did not change PUE and PUEstability. This finding was mainly due to the fact that the GLNG treatment had stronger influences on aboveground biomass (AGB), non-growing-season soil moisture (SMNG), temporal stability of AGB (AGBstability), temporal stability of non-growing-season air temperature (Ta_NG_stability), temporal stability of growing-season vapor pressure deficit (VPDG_stability) and temporal sta-bility of start of growing-season (SGSstability). Therefore, the warming scene with a higher non-growing-season-warming can have greater influences on PUE and PUEstability than the warming scene with a higher growing-season-warming, and there were possibly trade-offs between plant PUE and PUEstability under season-non-uniform-warming scenes in the alpine meadow.